Optimalisasi Penggunaan Media Digital dalam Pemasaran Produk pada Komunitas UMKM Kecamatan Cibungbulang - Prasasti Nuraeni; Mia Hermalian; Rio Kartika Supriatna; Evi Novita; Syaiful Anwar; Triana Oktafiani; Fitriani Fitriani (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service activity aims to improve the knowledge and skills of Micro, Small, and Medium Enterprises (MSMEs) in Cibungbulang District in optimizing the use of digital media for product marketing. The implementation method uses a participatory workshop with a project-based learning approach consisting of three stages: preparation (coordination with partners and needs mapping), implementation (interactive lectures, demonstrations, hands-on practice of content creation, and discussions), and evaluation (pre-test, post-test, and mentoring via WhatsApp group for one month). The results of the activity showed a significant increase in participant understanding from 32 percent (pre-test) to 85 percent (post-test). All participants successfully created business accounts on social media, 80 percent were able to optimize their business profiles, and 75 percent were able to access analytical features. Monitoring one month after the activity showed that 70 percent of participants consistently uploaded content regularly, with some participants reporting an increase in turnover of up to 25 percent. This activity recommended the need for follow-up workshops on product photography and copywriting, as well as expanding the scope of participants to other sub-districts in Bogor Regency.